Território e serviços de saúde pública: uma análise da estratégia saúde da família na cidade de Pirapora- Norte de Minas Gerais - Costa, Vanda Aparecida (2014)
The Unique health System has shown positive responses regarding the health problems of Brazilians. Very appropriate if you must the actions developed by the Family Health Strategy (FHS), adopted by the National policy of Basic Attention as strategy structuring this attention. In Pirapora, ESF makes a coverage of approximately 84,04% of the population, a number considered good by the Ministry of Health. The 15, 96% of the population who do not reside in the territories also receive basic care by professionals of the FHT, even not being registered. This research has as its general objective understand the organization of space from the dynamics of access to Family Health Strategy in the city of Pirapora, taking as its focus, analyze the territory and the territorialisation; analyze the ESF in the city; to discuss the access and affordability of the FHT with emphasis to the effectiveness and of the FHT. To achieve the objectives proposed we use different methodological procedures, among them: theoretical survey regarding the theme of the ESF and the concepts of territory, territorialism and network in health care. Data was collected and information in various governmental bodies, in the prefecture and in own health units in Pirapora. Interviews with managers of the FHT, Nurses, Nursing Technician, Community Health Agents and registered Families in ESF. It was found that the ESF has allowed the population of Pirapora greater access to health services, even so, there are needs for more interventions on the part of the manager and health professionals to try to reduce the health problems of the population, among them the infant mortality rate.